Tempting the Tempter - Huesman, Amy R., author.
1 online resource (236 pages)
Keywords: Tempting the Tempter considers how far fifteenth-century Italian mystics would go to imitate Christ, even in his encounters with the Devil in the desert. Elena of Udine, Caterina of Bologna, and Colomba of Rieti created their own desert experience through their austere devotional practices, and they suffered and overcame temptations from the Devil. This work explores how these women actively pursued encounters with the Devil, and how these private temptations prepared them for a public ministry of miracles, contributed to their perception as living saints, and allowed their biographers to promote them as true imitators of Christ, worthy of sainthood.